The action plan for river dolphins in South America - Duque Trujillo, Jose Fernando (2010)
To build the action plan, an international workshop was carried out at the city of Santa Cruz de La Sierra, Bolivia between the 21 and 23th of April 2008. Approximately 42 researchers and representatives from Governments of nine countries actively participated in the workshop. Initially, Dr. Enrique Crespo, Chairman of the Cetacean Specialist Group of the IUCN for Latinamerica presented an overview of the status of river dolphins. Following this, each country (Venezuela, Colombia, Ecuador, Peru, Bolivia and Brazil) made presentations of the status and conservations of theses species. Additionally, four presentations were made by experts on phylogeography and taxonomic status of river dolphins, Geographic Information System analysis of distribution, threats and research initiatives, Abundance estimation and, fisheries and conflicts in the Amazon River Basin.